Cell cycle profiling by image and flow cytometry: The optimised protocol for the detection of replicational activity using 5-Bromo-2'-deoxyuridine, low concentration of hydrochloric acid and exonuclease III - Ligasová, Anna; Konečný, Petr; Frydrych, Ivo; Koberna, Karel (PloS one, 2017)
The approach for the detection of replicational activity in cells using 5-bromo-2'-deoxyuridine, a low concentration of hydrochloric acid and exonuclease III is presented in the study. The described method was optimised with the aim to provide a fast and robust tool for the detection of DNA synthesis with minimal impact on the cellular structures using image and flow cytometry. The approach is based on the introduction of breaks into the DNA by the low concentration of hydrochloric acid followed by the subsequent enzymatic extension of these breaks using exonuclease III. Our data showed that the method has only a minimal effect on the tested protein localisations and is applicable both for formaldehyde- and ethanol-fixed cells. The approach partially also preserves the fluorescence of the fluorescent proteins in the HeLa cells expressing Fluorescent Ubiquitin Cell Cycle Indicator. In the case of the short labelling pulses that disabled the use of 5-ethynyl-2'-deoxyuridine because of the low specific signal, the described method provided a bright signal enabling reliable recognition of replicating cells. The optimized protocol was also successfully tested for the detection of trifluridine, the nucleoside used as an antiviral drug and in combination with tipiracil also for the treatment of some types of cancer.
Keywords: Flow Cytometry; Cell Cycle; Exodeoxyribonucleases; HeLa Cells; A549 Cells; bromodeoxyuridin; Bromodeoxyuridine; průtoková cytometrie; fluorescenční mikroskopie; Humans; buňky A549; exodeoxyribonukleasy; kyselina chlorovodíková; Microscopy, Fluorescence; Hydrochloric Acid; HeLa buňky; lidé; buněčný cyklus